Perceived stress, stigma, and social support among Nepali health care workers during COVID-19 pandemic: A cross-sectional web-based survey. - Lok Mani Giri; Kiran Paudel; Sandesh Bhusal; Tara Ballav Adhikari; Gabriel Gulis (Public Library of Science (PLoS), 2022)
The COVID-19 pandemic has caused immense psychological distress among Health Care Workers (HCWs). HCWs have been stigmatized by people at their workplace and community, fearing that health care workers are the sources of spreading the virus. This study aimed to assess the perceived stress, stigma, and social support of Nepali health care workers during the COVID-19 pandemic. A web-based cross-sectional survey was conducted among 380 Nepali HCWs. Perceived stress was measured using Perceived Stress Scale (PSS-10). The questionnaire related to stigma was derived from a study conducted to measure stigma among HCWs during the Middle East respiratory syndrome coronavirus (MERS-CoV) outbreak. Furthermore, perceived social support was measured by Oslo Social Support Scale (OSSS-3). Associated factors were examined using Chi-square tests followed by multivariate logistic regression analyses at the significance level of 0.05. This study illustrated that nearly half (44.2%) of the respondents perceived poor social support. Similarly, almost 3% of the HCWs experienced high perceived stress, whereas 87.6% perceived moderate stress, and 35% of the HCWs felt stigmatized. Nepali healthcare workers experienced perceived stress, social stigma, and social support in various severity levels during the COVID-19 pandemic. COVID-19 emergency is emotionally difficult and where psychological distress can jeopardize outcomes and affect work performance. Appropriate psychological interventions are needed to promote the mental well-being of the healthcare workers.